Is It Better to Kill Two Birds with One Stone? Internal Control Audit Quality and Audit Costs for Integrated versus Nonintegrated Audits - Gunn, Joshua L.; Li, Chan; Liao, Lin; Zhou, Shan (The Accounting Review, 2023)
ABSTRACT Audits of internal control over financial reporting (ICFR) are typically “integrated” with the audit of the financial statements (FSs)—both audits are conducted by the same audit firm, which designs procedures to satisfy the objectives of both audits simultaneously. A common assumption is that integrating the two audits is more effective and efficient than performing them separately. However, this assumption has not been tested empirically. Using a sample of Chinese companies that employ different audit firms for their FS and ICFR audits (i.e., nonintegrated auditors), we find evidence that challenges this assumption. Specifically, we find ICFR audit quality is higher for nonintegrated audits compared to integrated audits. Moreover, total audit fees are lower for nonintegrated audits, despite higher ICFR audit fees.